Correlation Analysis Study between Hearing Loss Occurence and Duration of Type 2 Diabetes Mellitus in Sultan Agung Islamic Hospital Semarang - Risyudhanti, Citta Arunika; Sulistyanto, Agung; Suparmi, Suparmi (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Introduction: Hearing impairment due to cochlear damage is one complication of Type 2 Diabetes Mellitus (DM2). Objective: This study aims to determine the relationship between duration of DM2 with hearing impairment.Method: The analytic observasional study with the cross sectional design using the medical record of DM2 outpatient in internal clinic of Islamic Sultan Agung Hospital Semarang and also pure tone audiometric examination’s record in Otorynolaryngology clinic of Islamic Sultan Agung Hospital Semarang.31 medical records of DM2 patients were meeting the inclusion and exclusion criteria. The data consist of 18 medical records of patients with less than6 years duration of DM2, and 13 medical records of patients with more than 6 years duration of DM2. The pure tone audiometry was used to classified the hearing impairment. The data analysis was conducted using SPSS 20.0. The correlation between the duration of DM2 and hearing impairment was analyzed using Chi Square test. The significance relation between the duration of DM type 2 and hearing impairment was analyzed using cooficient contigency, with significance of < 0.05. Result: hearing impairment’s distribution frequency on tested ears in Sultan agung Islamic Hospital Semarang were 27 ears having SNHL type (43,5%), 19 ears having CHL (30,6%) and 16 ears were normal (25,8%), p = 0,02 (p < 0,05). Conclusion: There is a weak correlation between the DM 2 duration and the incidence of hearing impairment in Sultan Agung Islamic Hospital Semarang.